2014
DOI: 10.1089/scd.2013.0497
|View full text |Cite
|
Sign up to set email alerts
|

Functional Assessment of Hematopoietic Niche Cells Derived from Human Embryonic Stem Cells

Abstract: To evaluate hematopoietic niche cell populations isolated from human embryonic stem cells (hESCs), we tested the ability of hESC-derived stromal lines to support CD34(+) umbilical cord blood (UCB)- and hESC-derived CD34(+)45(+) cells in long-term culture initiating cell (LTC-IC) assays. Specifically, these hematopoietic populations were cocultured with hESC-derived mesenchymal stromal cells (hESC-MSCs) and hESC-derived endothelial cells (hESC-ECs), and then assessed for their LTC-IC potential in comparison to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…26 Human umbilical cord blood (hUCB) samples were obtained from the University of Colorado Cord Blood Bank, ClinImmune Stem Cell Laboratory. 29…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…26 Human umbilical cord blood (hUCB) samples were obtained from the University of Colorado Cord Blood Bank, ClinImmune Stem Cell Laboratory. 29…”
Section: Methodsmentioning
confidence: 99%
“…M2-10B4 murine bone marrow stromal cells were purchased from the ATCC (Manassas, VA, USA) and maintained following established protocols (57). Samples of human umbilical cord blood (hUCB) were obtained from the ClinImmune Stem Cell Laboratory at the University of Colorado Cord Blood Bank (60).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have shown that mesenchymal cells can be differentiated from human pluripotent stem cells (hPSCs) ( Chin et al., 2016 , Ferrell et al., 2014 , Hoffman and Calvi, 2014 , Vodyanik et al., 2010 ). These previous studies identified mesenchyme as a single population defined mostly by expression of CD73 and/or CD105 and absence of hematopoietic and endothelial markers.…”
Section: Introductionmentioning
confidence: 99%
“…OP9 is typically used as a support for the differentiation of CD34 + cells from embryonic stem cells (ESCs) or pluripotent stem cells ( 18 – 21 ). Instead, M2-10B4 is a good support to maintain CD34 + cells in a long-term culture, acting like a hematopoietic niche ( 22 ). Our data show that these two culture conditions generated a large number of mature and functional NK cells.…”
Section: Introductionmentioning
confidence: 99%